2010
DOI: 10.1242/jeb.045914
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of visual pigments in caecilians (Amphibia: Gymnophiona), an order of limbless vertebrates with rudimentary eyes

Abstract: SUMMARYIn comparison with the other amphibian orders, the Anura (frogs) and Urodela (salamanders), knowledge of the visual system of the snake-like Gymnophiona (caecilians) is relatively sparse. Most caecilians are fossorial with, as far as is known any surface activity occurring mainly at night. They have relatively small, poorly developed eyes and might be expected to possess detectable changes in the spectral sensitivity of their visual pigments. Microspectrophotometry was used to determine the spectral sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 44 publications
2
35
0
Order By: Relevance
“…Opsin losses have occurred in other animals, including the American cockroach ( Periplaneta americana ) 28 , deep sea fish 29 , fossorial snakes 30 , caecilians 31 and both nocturnal and aquatic mammals 3234 . Such losses are typically associated with low-light or spectrally-attenuated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Opsin losses have occurred in other animals, including the American cockroach ( Periplaneta americana ) 28 , deep sea fish 29 , fossorial snakes 30 , caecilians 31 and both nocturnal and aquatic mammals 3234 . Such losses are typically associated with low-light or spectrally-attenuated environments.…”
Section: Discussionmentioning
confidence: 99%
“…Among other vertebrates, rod monochromatic taxa are rare and to our knowledge have only been documented in bony and cartilaginous fishes [73][81], caecilians [22], [82], and the cave salamander Proteus anguinus [83], although presumed rod monochromacy based entirely on immunocytochemistry, microscopy or spectral analysis does not preclude the possibility that other minor visual pigment classes exist [77], [81], [83]. Most of the rod monochromatic fish species inhabit the deep sea or are nocturnal; caecilians are generally fossorial and/or nocturnal with poorly developed eyes; and the cave salamander Proteus lives in a virtually light-free environment.…”
Section: Discussionmentioning
confidence: 99%
“…In the open marine environment, the electromagnetic radiation of visible light is weakened with depth due to absorption and scattering [89]. In the mesopelagic zone (150–1000 m), down-welling sunlight becomes more monochromatic and the spectrum shifts towards shorter, bluer wavelengths with depth [81], [82]. Below 1000 m (bathypelagic zone), there is no down-welling sunlight and localized bluish bioluminescence becomes the predominant source of light [90].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the Hottentot golden mole has inactivated copies of both cone opsins, and PDE6C is disrupted in other sloths and armadillos 18 20. Beyond mammals, retinal spectrophotometry has identified rod-only retinas in cartilaginous and bony fishes62 and subterranean amphibians known as caecilians 63. Furthermore, retinal mRNA analyses have demonstrated that some burrowing snakes lack cones,64 and retinal immunohistochemistry revealed that at least a single population of cave-dwelling salamanders has lost cones 65.…”
Section: Amelogenesis Imperfectamentioning
confidence: 99%